2000
DOI: 10.1016/s0920-1211(99)00108-4
|View full text |Cite
|
Sign up to set email alerts
|

Felbamate block of recombinant N-methyl-d-aspartate receptors: selectivity for the NR2B subunit

Abstract: The anticonvulsant felbamate blocks N-methyl-D-asparate (NMDA) receptors but fails to exhibit the neurobehavioral toxicity characteristic of other NMDA receptor antagonists. To investigate the possibility that felbamate's favorable toxicity profile could be related to NMDA receptor subtype selectivity, we examined the specificity of felbamate block of recombinant NMDA receptors composed of the NR1a subunit and various NR2 subunits. Felbamate produced a rapid, concentration-dependent block of currents evoked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 27 publications
1
53
0
Order By: Relevance
“…Inhibition by dynorphin A Mott et al (1998). Values for eliprodil are from Avenet et al (1997), and values for felbamate are from Harty and Rogawski (2000). Values for haloperidol are from Ilyin et al (1996).…”
Section: E Noncompetitive Antagonistsmentioning
confidence: 99%
“…Inhibition by dynorphin A Mott et al (1998). Values for eliprodil are from Avenet et al (1997), and values for felbamate are from Harty and Rogawski (2000). Values for haloperidol are from Ilyin et al (1996).…”
Section: E Noncompetitive Antagonistsmentioning
confidence: 99%
“…However, these recording indicate that the drug may allosterically block NMDA receptors with a specific action on receptors containing the NR2B subunit. If this observation can be confirmed, lacosamide would have some similarity with felbamate, which also is a low affinity antagonist of NMDA receptors with a preference for the NR2B subunit Harty and Rogawski, 2000). Lacosamide has good oral bioavailability (~100%), linear pharmacokinetics, a half-life (~12 h) that will allow twice-daily dosing, insignificant protein binding (<1%), and its metabolites are largely eliminated by the kidney so that there are no significant interactions with other AEDs (Hovinga, 2003).…”
Section: Functionalized Amino Acidsmentioning
confidence: 98%
“…In addition, felbamate at a concentration of 100 μM has been found to block NMDA receptor mediated synaptic responses (Pugliese et al, 1996) and to inhibit NMDA receptor currents in isolated neurons (K d , ~1 mM; Rho et al, 1994;Subramaniam et al, 1995;Kuo et al, 2004). Studies with recombinant NMDA receptor subunit combinations have indicated that felbamate selectively bocks NMDA receptors composed of NR2B subunits at lower concentrations (IC 50 , 0.5 mM), than other subunit combinations Harty and Rogawski, 2000). This selectivity could contribute to the relatively low neurobehavioral toxicity of felbamate in relation to other NMDA receptor antagonists (Löscher and Rogawski, 2002).…”
Section: Carbamates: Flurofelbamate and Rwj-333369mentioning
confidence: 99%
“…271 Studies with recombinant NMDA receptors have indicated that felbamate preferentially blocks NMDA receptors containing NR2B subunits. 272,273 The drug acts as an allosteric modulator of channel gating, 274 with a preferential action to stabilize the inactivated state so as to produce a usedependent block. 275 This use-dependent action may selectively inhibit NMDA receptors that are excessively activated as is believed to occur during seizure discharges.…”
Section: Ionotropic Glutamate Receptorsmentioning
confidence: 99%